Assessment of undercut defect in a laser welded plate made of Ti–6Al–4V titanium alloy with probabilistic domain failure assessment diagram. (January 2016) - Jallouf, S.; Casavola, K.; Pappalettere, C.; Pluvinage, G.
Abstract: A domain failure assessment diagram has been used to assess an undercut defect in a laser welded plate made of Ti–6Al–4V titanium alloy and to compute the probability of failure. Evaluations of the safety factor and uncertainty with the assessment angle have been obtained. The low probability of failure indicates that laser welding is a safe process for aeronautical components which need a high level of reliability. Highlights: A domain failure assessment diagram has been used to assess an undercut defect in a laser welded plate made of Ti–6Al–4V titanium alloy. The probability of failure has been computed. Evaluations of the safety factor and uncertainty with the assessment angle have been obtained.